What is cybersecurity for? - Stevens, Tim, 1973- (What is it for?, 2023)
How will protecting our digital infrastructure shape our future? Cybersecurity is one of the key practical and political challenges of our time. It is at the heart of how modern societies survive and thrive, yet public understanding is still rudimentary: media portrayals of hoodie-wearing hackers accessing the Pentagon don't convey its complexity or significance to contemporary life. This book addresses this gap, showing that the political dimension is as important as the technological one. It accessibly explains the complexities of global information systems, the challenges of providing security to users, societies, states and the international system, and the multitude of competing players and ambitions in this arena. Making the case for understanding it not only as a technical project, but as a crucial political one that links competing visions of what cybersecurity is for, it tackles the ultimate question: how can we do it better?